The influence of personality features in choosing the profession - Calin, Mariana Floricica; Sandu, Mihaela Luminita; Saucă (Borș), Filotia (Technium Social Sciences Journal, 2021)
A profession or trade is a permanent occupation, an activity based on specialized education that someone regularly pursues on the basis of an appropriate qualification, in order to obtain remuneration. Personality is a universe that constantly encourages knowledge, but which can never be exhausted. Goethe believed that the supreme performance of scientific knowledge is the knowledge of man. The idea is justified both by the maximum complexity of the human being and by the fact that "man represents the supreme value for man." Between Nietzsche's pessimism, which states that "man is the animal that can never be defined," and Protagoras' axiological view, that "man is the measure of all things," personality is a global concept, a structure that cannot be defined only by its structural elements. The concept of interest and its implications for human learning and development have an important role in both education and psychology. In a society that continues to transform, social, economic and psychological factors cause profound changes in the sphere of professions and occupations. Therefore, there must be a transition to a training school and an appropriate way so that anyone can meet the requirements in a constantly changing society.